Wykonanie i respektowanie polskiego Konkordatu z 1993 r. Wybrane zagadnienia w ujęciu krytycznym - Borecki, Paweł (Studia Prawa Publicznego, 2024)
Since the preparation of a critical report in 2012 on the respect for the Polish Concordat of 1993, the factual and legal situation in this area has not improved until the present day. Moreover, new circumstances have arisen, indicating the failure to implement the Treaty and its violation. These negative phenomena concerned the leading principles of the agreement with the Vatican, but also the specific detailed provisions of the agreement in question. They intensified between 2015 and 2023. This was committed by both the state authorities and the church side, including even the Holy See. In practice, the Concordat of 1993 has a kind of symbolic function, because it indicates the special position of Catholicism and the Catholic Church in Poland after 1989. It also plays a guarantee role, but to a limited extent. Its normative function is clearly reduced. The Treaty does not regulate a number of key issues for Catholics and church institutions in Poland. The agreement with the Vatican has not yet been supplemented by additional agreements between the Parties or agreements between the Government of the Republic of Poland and the authorized Polish Episcopal Conference. The Concordat did not ensure the loyalty of the domestic institutional Church to the system of a democratic state under the rule of law. The period 2015–2023, however, saw an instrumentalization of religion and the Church by the political decision-makers of the time, contrary to the fundamental principles of this system. The limited degree of implementation and compliance with the 1993 Treaty is evidence of the low legal culture in religious matters in the Third Republic. No improvement in this area should be expected in the near future.